Teacher Work Stress and Psychological Well-being - Diah Sastaviana; Alexander Indrakusuma Linggi (CV. Ulil Albab Corp, 2025)
The aims of this research is to find the relationship between job stress and teacher’s psychological well-being. The approach methods used in this research are correlational quantitative method and measurement instrument using job stress and psychological well-being scale. The sampling techniques used are simple random sampling and the number of subjects obtained were 83 teachers. The data analysis technique used in the hypothesis testing was Pearson Product Moment analysis. The results of the analysis is the correlation value R = -0,678 with a significance value of 0.000 (p <0.01). Based on the result, it can be concluded that there is a strong negative relationship between job stress and psychological well-being. The conclusion of this research show that increasing job stress can resulting in a decrease in psychological well-being. So that, job stress has an impact on the psychological well-being of teachers.